Hepatic effects of the clomazone herbicide in both its free form and associated with chitosan-alginate nanoparticles in bullfrog tadpoles - Oliveira, Cristiane Ronchi de [UNESP]; Fraceto, Leonardo Fernandes [UNESP]; Rizzi, Gisele Miglioranza; Salla, Raquel Fernanda; Abdalla, Fábio Camargo; Costa, Monica Jones; Silva-Zacarin, Elaine Cristina Mathias (Elsevier, 2016)
The use of agrochemicals in agriculture is intense and most of them could be carried out to aquatic environment. Nevertheless, there are only few studies that assess the effects of these xenobiotics on amphibians. Clomazone is an herbicide widely used in rice fields, where amphibian species live. Thus, those species may be threatened by non-target exposure. However, nanoparticles are being developed to be used as a carrier system for the agrochemicals. Such nanoparticles release the herbicide in a modified way, and are considered to be more efficient and less harmful to the environment. The aim of this study was to comparatively evaluate the effect of clomazone in its free form and associated with nanoparticles, in the liver of bullfrog tadpoles (Lithobates catesbeianus) when submitted to acute exposure for 96 h. According to semi-quantitative analysis, there was an increase in the frequency of melanomacrophage centres, in the accumulation of eosinophils and in lipidosis in the liver of experimental groups exposed to clomazone - in its free form and associated with nanoparticles - in comparison with the control group, and the nanotoxicity of chitosan-alginate nanoparticles. The increase of melanomacrophage centres in all exposed groups was significant (P < 0.0001) in comparison to control group. Therefore, the results of this research have shown that exposure to sublethal doses of the herbicide and nanoparticles triggered hepatic responses. Moreover, these results provided important data about the effect of the clomazone herbicide and organic nanoparticles, which act as carriers of agrochemicals, on the bullfrog tadpole liver.
Keywords: Ecotoxicology; Frog; Lipidosis; Liver; Melanomacrophage centres; Nanotoxicity